Impactos de reduç\~oes compensadas na tributaç\~ao da renda do setor produtivo: Uma avaliaç\~ao com um modelo de geraç\~oes superpostas - Marco Antônio Freitas de Hollande Cavalcanti; Napole\~ao Luiz Costa da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper aims to contribute to the debate on the best way to reduce the tax burden on the production sector in Brazil, by simulating an overlapping generations model calibrated to the country's economy. Our focus is on the comparison of the macroeconomic and welfare impacts brought about by policies that reduce the tax burden on labour and policies based on the reduction of the tax burden on capital. According to our results, reducing the tax burden on capital may lead to substantial gains in terms of capital accumulation and GDP relative to reducing the burden on labour. Both types of policies must generate welfare losses to elderly generations alive when the reform takes place and welfare gains to future generations, but the effects on intermediate generations may differ substantially under each policy.
Keywords: E60; H20; 330; Steuerbelastung; Industrie; Overlapping Generations; Simulation; Brasilien